2016
DOI: 10.1002/adv.21779
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Mechanical, and Thermal Characterization of Poly(Lactic Acid)/Cellulose Multifilament Fibers Prepared by Melt Spinning

Abstract: In this study, multifilament fibers based on neat poly(lactic acid) (PLA), PLA/cellulose nanowhiskers (CNWs), and PLA/cellulose microcrystalline (MCC) loaded at 1 and 3 wt.% were prepared by melt-spinning process in the presence of PLA-grafted maleic anhydride (PLA-g-MA) used as the compatibilizer and PEG as the plasticizer. This study showed that the incorporation of MCC in PLA matrix whatever the loading rate was not suitable for multifilament fibers spinning compared with CNW, due to the restricted drawabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…This was attributed to the improved compatibility observed between PLA and C-6 modified CNCs. PLA-grafted maleic anhydride (PLA-g-MA) as compatibilizer for CNCs/microcrystalline cellulose (MCC) and PLA in the fabrication of PLA composite fibers, was recently reported by Aouat et al [83]. It was reported that small aggregations of CNCs were visible on the PLA/PLA-g-MA/CNC (1 wt %) surface, which became more pronounced in PLA/PLA- g -MA/MCC (1 wt %).…”
Section: Composites Preparationmentioning
confidence: 99%
“…This was attributed to the improved compatibility observed between PLA and C-6 modified CNCs. PLA-grafted maleic anhydride (PLA-g-MA) as compatibilizer for CNCs/microcrystalline cellulose (MCC) and PLA in the fabrication of PLA composite fibers, was recently reported by Aouat et al [83]. It was reported that small aggregations of CNCs were visible on the PLA/PLA-g-MA/CNC (1 wt %) surface, which became more pronounced in PLA/PLA- g -MA/MCC (1 wt %).…”
Section: Composites Preparationmentioning
confidence: 99%
“…PLA-grafted maleic anhydride (PLA-g-MA) as compatibilizer for CNCs/microcrystalline cellulose (MCC) and PLA in the fabrication of PLA composite fibers, was recently reported by Aouat, et al [63]. It was reported that small aggregations of CNCs were visible on the PLA/PLA-g-MA/CNC (1wt%) surface, which became more pronounced in PLA/PLA-g-MA/MCC (1wt%).…”
Section: Melt Spinningmentioning
confidence: 93%
“…Microcrystalline cellulose (MCC) was supplied by Sigma-Aldrich under the trade name Avicel PH 101. MCC was also used as the raw material for extracting cellulose nanowhiskers (CNW) by using sulfuric acid hydrolysis in aqueous media (Aouat et al, 2018). Sulfuric acid 95-97% was purchased from Sigma-Aldrich.…”
Section: Materials Usedmentioning
confidence: 99%
“…In the second step, the pellets were used to obtain the multifilament fibers using a melt-spinning machine, Model Spinboy I, manufactured by Busschaert Engineering. Elaboration of PLA fibers has been detailed in a recent paper (Aouat et al, 2018).…”
Section: Preparation Of Pla/cellulose Bionanocompositesmentioning
confidence: 99%
See 1 more Smart Citation